THEORETICAL ASPECTS OF THE PERSONALITY COMMUNICATIVE POTENTIAL INVESTIGATION - Solovey, Oksana Anatolievna (Psychological Prospects Journal, 2013)
The article reveals the essence of the concepts of "potential", "communicative potential". The approaches to the study of communicative potential are analyzed, its main components and characteristics are singled out. The structure of the communicative potential of the individual through the prism of the communicative nucleus and the communicative world of the personality are described.